Comparison of the glucagon‐like‐peptide‐1 receptor agonists dulaglutide and liraglutide for the management of diabetes in solid organ transplant: A retrospective study. Issue 5 (5th February 2020) - Singh, Priyamvada; Taufeeq, Maryam; Pesavento, Todd E.; Washburn, Kenneth; Walsh, Debbie; Meng, Shumei
Abstract: Glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) are gaining popularity in the management of diabetes in solid organ transplant (SOT) recipients. There are no studies available comparing the two GLP‐1RAs dulaglutide and liraglutide in SOT. We performed a retrospective chart review to assess the safety and effectiveness of these agents in adult SOT with diabetes at 6, 12 and 24 months. There were 63 and 25 recipients on dulaglutide and liraglutide, respectively. There was a sustained reduction in primary endpoints of weight, BMI and insulin requirement with dulaglutide when compared to liraglutide. Decrease in weight was 2%, 4% and 5.2% with dulaglutide and 0.09%, 0.87% and 0.89% with liraglutide at 6, 12 and 24 months respectively. BMI reduction followed the same trend in the two groups. The percentage reduction for insulin was 26% with dulaglutide and 3.6% with liraglutide. There was a 10% reduction in creatinine and a 15% increase in estimated glomerular filtration rate (eGFR) at the end of 24 months with dulaglutide. However, there was an increase in creatinine by 7% and an 8% decrease in eGFR at the end of 24 months with liraglutide.